Early Effects of Aβ Oligomers on Dendritic Spine Dynamics and Arborization in Hippocampal Neurons - Ortiz-Sanz, Carolina; Gaminde-Blasco, Adhara; Valero, Jorge; Bakota, Lidia; Brandt, Roland; Zugaza, José L.; Matute, Carlos; Alberdi, Elena (Frontiers in Synaptic Neuroscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disorder that leads to impaired memory and cognitive deficits. Spine loss as well as changes in spine morphology correlates with cognitive impairment in this neurological disorder. Many studies in animal models and ex vivo cultures indicate that amyloid beta peptide (Abeta) oligomers induce synaptic damage early during the progression of the disease. Here, in order to determine the events that initiate synaptic alterations, we acutely applied oligomeric Abeta to primary hippocampal neurons and an ex vivo model of organotypic hippocampal cultures from mouse after targeted expression of EGFP to allow high-resolution imaging and algorithm-based evaluation of spine changes. Dendritic spines were classified as thin, stubby or mushroom based on morphology. In vivo time-lapse imaging showed that the three spine types were relatively stable, although their stability significantly decreased after treatment with Abeta oligomers. Unexpectedly, we observed that the density of total dendritic spines increased in organotypic hippocampal slices treated with Abeta compared to control cultures. Specifically, the fraction of stubby spines significantly increased, while mushroom and thin spines remained unaltered. Pharmacological tools revealed that acute Abeta oligomers induced spine changes through mechanisms involving CaMKII and integrin beta1 activities. Additionally, analysis of dendritic complexity based on a 3D reconstruction of the whole neuron morphology showed an increase in the apical dendrite length and branching points in CA1 organotypic hippocampal slices treated with Abeta. In contrast to spines, the morphological changes were affected by integrin beta1 but not by CaMKII inhibition. Altogether, these data indicate that Abeta oligomers exhibit early dual effects by acutely enhancing dendritic complexity and spine density.